Longitudinal Trends in Resource Utilization in an Incident Cohort of Open Angle Glaucoma Patients: Resource Utilization in Open Angle Glaucoma - Stein, Joshua D. (2012)
PURPOSE: To characterize the costs of caring for patients with open-angle glaucoma (OAG) in the United States (US) over time and to identify factors that influence these costs. DESIGN: Longitudinal cohort study. METHODS: Claims data from 19,927 newly-diagnosed OAG patients enrolled in a large US managed care network were reviewed to identify glaucoma-related charges for all incident OAG patients from 2001–2009. Average glaucoma-related charges for enrollees with OAG were characterized in six month blocks from the date of initial OAG diagnosis through the following 5 years. Factors associated with being an enrollee in the costliest 5% for glaucoma-related charges (accruing ≥$5810 in charges in the first 2 years) were identified using logistic regression. RESULTS: The costliest 5% of enrollees were responsible for $10,202,871 (24%) of all glaucoma-related charges. By comparison, those whose costs fell within the lower 50% of the cost distribution collectively amassed only $7,986,582 (19%) of all glaucoma-related charges. A spike in glaucoma-related charges occurred in the 6 month period around the time of OAG diagnosis, stabilized by 1 year following diagnosis, and remained relatively constant over time. Risk factors associated with being in the costliest 5% for glaucoma-related care included younger age, Northeastern US state residence, undergoing cataract surgery, and possessing ocular co-morbidities.(p<0.006 for all comparisons). CONCLUSIONS: A small subset of enrollees account for a large proportion of all glaucoma-related charges. Understanding the characteristics of these individuals and finding ways to reduce disease burden and costs associated with their care can result in substantial cost savings.